2014
DOI: 10.1111/cod.12307
|View full text |Cite
|
Sign up to set email alerts
|

Contact sensitization to modern dressings: a multicentre study on 354 patients with chronic leg ulcers

Abstract: Sensitization to MDs is not rare. It is absolutely necessary to label all components of MDs on their packaging and to avoid some sensitizing molecules, such as colophonium derivatives or any strong sensitizers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 30 publications
2
35
0
1
Order By: Relevance
“…Allergic contact dermatitis to synthetic rubber, neoprene, in compression stockings has been reported . Modern dressing‐related contact dermatitis is infrequent but has also been reported . Usage of these modern dressings is infrequent in Indian patients, and hence, sensitisation may be a rare occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic contact dermatitis to synthetic rubber, neoprene, in compression stockings has been reported . Modern dressing‐related contact dermatitis is infrequent but has also been reported . Usage of these modern dressings is infrequent in Indian patients, and hence, sensitisation may be a rare occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…2 The North American Contact Dermatitis Group identified that 1.5% to 9.1% of patch-tested patients older than 20 years are allergic to bacitracin, and 7.2% to 13.1% of patch-tested patients older than 20 years have allergic sensitization to neomycin. 6 The number of positive patch test was correlated with the duration of ulcerative disease and independent of ulcer etiology (venous, arterial, or mixed arteriovenous). 6 The number of positive patch test was correlated with the duration of ulcerative disease and independent of ulcer etiology (venous, arterial, or mixed arteriovenous).…”
Section: Review Of the Current Literaturementioning
confidence: 93%
“…[3][4][5] In a recent study on 354 patients with CLUs, the percentage of positive patch test to modern wound-related materials was reported as high as 59.6%. 6 The top 5 common allergens in 5 studies from 2009 to 2015 include balsam of Peru, lanolin, amerchol, fragrance mix, and benzocaine (Table 2). 6 The top 5 common allergens in 5 studies from 2009 to 2015 include balsam of Peru, lanolin, amerchol, fragrance mix, and benzocaine (Table 2).…”
Section: Review Of the Current Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Around 70 % of patients with chronic wounds showed at least one contact sensitization when undergoing patch testing (27). Duration of ulcerative diseases, frequent use of different topical ointments for the surrounding skin and numerous changes in wound dressing materials are seen as risk factors for contact dermatitis.…”
Section: Inflammatory Skin Diseasesmentioning
confidence: 99%